Meloidogyne exigua (Meloidogynidae) in rubber tree clones during two periods of the year - Pezzoni-Filho, Jose Carlos [UNESP]; De Brida, Andressa Lima [UNESP]; De Campos-Moraes, Diego Augusto [UNESP]; Siciliano-Wilcken, Silvia Renata [UNESP]; Lopes-Zimback, Celia Regina [UNESP]; Luiz-Furtado, Edson [UNESP] (Corporacion Colombiana de Investigacion Agropecuaria (Corpoica), 2018)
Meloidogyne exigua Goeldi, race 3 (Nematoda: Tylenchida: Meloidogynidae), has become an important pest for rubber tree plantations. Thus, the objective of this work was to monitor its infestation in rubber tree plantations and to determine the spatial distribution of the population in the roots of clones GT 1 and RRIM 600, without identification of the rootstock, in two periods of 2013, in the municipality of Itiquira, MT, Brazil. In May, 264 samples were collected, and in November, 227 samples were collected in the total area of 6,646 hectares planted with 22 clones, which were used for the interpolation by the kriging method for mapping infestations in the total area. Based on this planting map, the plots of the two evaluated clones were cut, resulting in 55 samples in May (clone GT 1 = 29 and RRIM 600 = 26 samples) and 52 in November (clone GT 1 = 27 and RRIM 600 = 25 samples), in a total area of 2,409 hectares. With a GNSS device, each sampling point was identified, and roots of the rubber tree were collected at 0.10 m depth. For the two clones, the infestations in May were larger than those recorded in November. The Spatial Dependency Index (IDE) between collections collected in May and November of 2013 were moderate. The cross-validation of the data was not satisfactory, due to the high variation of infestations.
Keywords: Geostatistics; Hevea brasiliensis; Interpolation; Kriging; Root-knot nematode